Association between clinical diagnosis of foetal distress with umbilical artery acidaemia at birth in women undergoing caesarean section for foetal distress - Gandhi, Garima; Chandnani, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The risks of maternal morbidity and mortality associated with a caesarean section may not be reasonably justified by the degree of neonatal compromise at birth associated with caesarean section done for clinically diagnosed foetal distress. The aim was to study the association of clinical diagnosis of non-reassuring foetal status with umbilical artery acidaemia at birth in women undergoing caesarean section for foetal distress and to evaluate outcomes in neonates born by caesarean section performed for foetal distress. Methods: Prospective observational study of all the women undergoing emergency caesarean section for foetal distress at a tertiary care teaching facility over 2 months. Criteria for diagnosis of foetal distress were thick meconium stained liquor only or foetal heart rate abnormality with or without meconium stained liquor. Testing for pH was done on arterial blood drawn from umbilical cord at the time of birth. Acidaemia was defined as cord blood pH less than 7.2. Severe acidaemia was defined as cord blood pH less than 7.0. Results: Cord blood pH was analysed in 110 caesareans done for foetal distress. Incidence of neonatal acidaemia at birth in study population was 53.6%. Conclusions: Much lower incidence of actual acidaemia and low Apgar scores in neonates born by caesarean section done for clinical diagnosis of foetal distress than previously reported indicate the need for more stringent criteria and more objective tests for diagnosis of foetal distress.